2018
DOI: 10.1111/jpm.12454
|View full text |Cite
|
Sign up to set email alerts
|

The association of nursing care perception with coping skills and posttraumatic growth in mental disorders

Abstract: Introduction Although it is recognized that suffering a mental illness is a traumatic experience, the fact that this can lead to posttraumatic growth and the variables that may affect the situation are rarely discussed in the literature. Aim This study was conducted to determine the effects of coping styles and nursing care perceptions on posttraumatic growth in mental disorders. Method The descriptive study was conducted at a psychiatric clinic with a personal information form and three-scale test. Results In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…For PTG, the direct association was positive for “no unresolved/untreated symptoms,” negative for “satisfaction with care for other diseases,” and there was no effect for “satisfaction with cancer care.” These findings are different from a previous study, 12 which found that satisfaction with nursing care was related to higher PTG. One possible explanation for this discrepancy is that the previous study specifically focused on nursing care, but our study assessed medical care in general.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For PTG, the direct association was positive for “no unresolved/untreated symptoms,” negative for “satisfaction with care for other diseases,” and there was no effect for “satisfaction with cancer care.” These findings are different from a previous study, 12 which found that satisfaction with nursing care was related to higher PTG. One possible explanation for this discrepancy is that the previous study specifically focused on nursing care, but our study assessed medical care in general.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, greater satisfaction of needs and more positive cognitive appraisal could promote PTG 11 ; satisfaction with nursing care was related to more PTG among inpatients. 12 A recent longitudinal study found a relation between BF and improved psychological functioning in cancer survivors (mean time postdiagnosis <5 years) who were receiving psychological care. 13 However, those studies neither focused on LTCS nor considered the role of cancer distress.…”
Section: Cognitive Appraisal Of Medical Care and Bf/ptgmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have also shown that coping with stressful situations is directly related to posttraumatic growth (Guo, Fu, Xing, Qu, & Wang, 2017; Nisa & Rizvi, 2016; Şimşek Arslan & Buldukoglu, 2018). For instance, Şimşek Arslan and Buldukoglu (2018) showed that people with a mental disorder who have effectively coped with stressful conditions have a higher posttraumatic growth (, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that coping with stressful situations is directly related to posttraumatic growth (Guo, Fu, Xing, Qu, & Wang, 2017;Nisa & Rizvi, 2016;S¸ims¸ek Arslan & Buldukoglu, 2018). For instance, Ş ims¸ek Arslan and Buldukoglu (2018) showed that people with a mental disorder who have effectively coped with stressful conditions have a higher posttraumatic growth (, 2018). Similarly, in their study of the survivors of the Wenchuan earthquake in China, Guo et al (2017) showed that the use of coping strategies was associated with posttraumatic growth.…”
mentioning
confidence: 99%